2016
DOI: 10.4236/jamp.2016.42038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonlinear Thermal Radiation on Boundary Layer Flow of Viscous Fluid over Nonlinear Stretching Sheet with Injection/Suction

Abstract: The present study reveals the effect of nonlinear thermal radiation and magnetic field on a boundary layer flow of a viscous fluid over a nonlinear stretching sheet with suction or an injection. Using suitable similarity transformations, governing partial differential equations were reduced to higher order ordinary differential equations and further these are solved numerically using of Keller-Box method. Effect of flow controlling parameter on velocity, temperature and nanoparticle fluid concentration, local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…They reported that both the radiation and temperature ratio parameters have the tendency to influence a hike in the thermal field. A Keller box technique is employed by Laxmi and Shankar 33 to examine the impact of nonlinear radiation on a boundary layer flow with a variable magnetic field. Some pieces of literature associated with the nonlinear radiation effect are in [34][35][36][37][38] .…”
Section: Features Of Entropy Optimization On Mhd Couple Stress Nanoflmentioning
confidence: 99%
“…They reported that both the radiation and temperature ratio parameters have the tendency to influence a hike in the thermal field. A Keller box technique is employed by Laxmi and Shankar 33 to examine the impact of nonlinear radiation on a boundary layer flow with a variable magnetic field. Some pieces of literature associated with the nonlinear radiation effect are in [34][35][36][37][38] .…”
Section: Features Of Entropy Optimization On Mhd Couple Stress Nanoflmentioning
confidence: 99%
“…The transfer of heat and flow of the visco‐elastic fluid with viscous dissipation under the nonlinearity of the stretching sheet was taken up by Nandeppanavar et al 24 The result was that the rate of transfer of heat can be controlled by selecting some appropriate parametric values for the visco‐elasticity, the Eckert and the Prandtl numbers. The effect of nonlinear thermal radiation with suction/injuction tendencies and taking the magnetic field into account due to nonlinearity of the stretching sheet was investigated by Laxmi and Shankar 25 . Khan et al 26 addressed the phenomena of transfer of heat and mass of Maxwell fluid flow caused by nonlinearity of the stretching surface with homogeneous/hetrogeneous reactions and internal heat absorption/generation source.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nonlinear thermal radiation with suction/injuction tendencies and taking the magnetic field into account due to nonlinearity of the stretching sheet was investigated by Laxmi and Shankar. 25 Khan et al 26 addressed the phenomena of transfer of heat and mass of Maxwell fluid flow caused by nonlinearity of the stretching surface with homogeneous/hetrogeneous reactions and internal heat absorption/ generation source. Recently, Elbashbeshy et al 27 evaluated the transfer of heat and flow with heat generation effects for Maxwell fluid over a stretching surface of variable thickness.…”
mentioning
confidence: 99%
“…Characteristics of non-linear thermal radiation and magnetic field flow of Sisko nanofluid has been studied by Soomro et al [14]. Laxmi and Shankar [15] analyzed the radiative flow of viscous fluid in the frame of injection/suction. Some prominent literature for non-linear thermal radiation can be studied in the refs.…”
Section: Introductionmentioning
confidence: 99%